Exploring the financial footprints of NCIP - Dacanay, Santos Jose III O. (Cordillera Review : Journal of Philippine Culture and Society, 2011)
This paper adds to a growing literature concerned with the instrumentality of annual appropriations, audited financial reports and development approaches, and the consequences of their adoption and use within State-Indigenous Community relations. It explores a single case of how the National Commission on Indigenous Peoples (NCIP), a government agency tasked with the overall recognition and protection of indigenous peoples' and communities' (IPs/ICCs) rights in the Philippines, use these instruments in pursuit of its rights-based and multi-stakeholder agenda. The article examines how the NCIP navigates through state-imposed instruments and involves the idea of institutional footprints where an organization leaves marks where it has been active, which can be studied to give clues both about the organization itself and the effect of its actions. This exploratory study on financial footprints finds heavy fiscal dependence of NCIP on the state, a huge personnel burden, weak financial control measures, poor absorptive capacity and lack in readiness of selected project partners, and pronounced regional disparity and inequity in fund allocation and service delivery. The transition from incremental to performance-based, then to zero-based, budgeting, and the adoption of the rights-based approach show how the adoption of state instruments reshape the focus and priority of NCIP. The harmonization and interface of the proposed IP Master Plan 2012-2016 with the Philippine Development Plan 2011-2016 provides a renewed challenge for advancing IP and ICC rights and well-being as a test case for inclusive growth.